Analisis Efektivitas, Kontribusi, dan Strategi Optimalisasi Pajak Restoran dan Pajak Hotel dalam Mendukung Pendapatan Asli Daerah Kota Bogor - Nazira Yuniar Asri Yanti; Hafifah Nasution; Putri Haryani (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2026)
This study aims to analyze the effectiveness, contribution, and optimization strategies of Restaurant Tax and Hotel Tax in supporting the sustainability of Local Own-Source Revenue (PAD) of Bogor City. The study employed a descriptive method with a quantitative approach supported by qualitative data. The results indicate that the effectiveness levels of Restaurant Tax and Hotel Tax in Bogor City were categorized as highly effective, with average effectiveness ratios of 107.24%, and 117.74%, respectively. However, the contribution of Restaurant Tax to Local Own-Source Revenue was only 13.55%, which falls into the less contributive category, while the contribution of Hotel Tax was 8.03%, categorized as very low contributive. Based on the SWOT analysis, the reccomended optimization strategies include expanding the tax base through taxpayer data collection and updating, optimizing digital-based payment and monitoring systems, enhancing human resource capacity, strenghening tax education and outreach programs, developing risk based supervision, and improving inter agency cooperation. The implementation of these strategies is expected to increase the revenue and contribution of Restaurant Tax and Hotel Tax in supporting the sustainability of Bogor City’s Local Own-Source Revenue.